Development of the assessment of adaptation difficulty in elder (AADE) scale - ŞİŞMAN, FATMA NEVİN (My University, 2012)
Objectives: The aim of this study was to develop the Assessment Scale of Adaptation Difficulty for the Elderly and determine its reliability and validity. Methods: The study sample was comprised of 309 elderly participants aged 65 and older living in 2 nursing homes. The theoretical framework for the scale was the Roy Adaptation Model. The construct validity of the scale was tested using exploratory factor analysis, and reliability was assessed using internal consistency and split-half reliability. Results: The content validity index of the scale was 98.54 %. Factor analysis yielded 4 factors with eigenvalues of 1 and above, which explained 65.57% of the total variance. The alpha coefficient for the scale was 0.93. Cronbach’s alpha values were 0.88 for the first half and 0.89 for the second half; the Guttman Cronbach’s alpha value was 0.83. Conclusion: The final scale consists of 24 items answered on a 4-point Likert-type scale. The scale is evaluated on the basis of a mean score; the lowest score possible is 0 and the highest is 3. The closer the individual’s score is to 0, the higher the level of adaptation. The current study found good reliability and validity for the scale. It is recommended for use in determining the extent of adaptation difficulties of the elderly. Amaç: Bu çalışmanın amacı Yaşlılarda Uyum Güçlüğünü Değerlendirme Ölçeği’nin geliştirilmesi, geçerlik ve güvenirliğinin belirlenmesidir. Gereç ve Yöntem: Araştırmanın örneklemini iki huzurevinde yaşayan 65 yaş ve üstü 309 yaşlı birey oluşturdu. Ölçeğin kuramsal çerçevesini Roy Adaptasyon Modeli oluşturdu. Ölçeğin yapı geçerliği faktör analizi kullanılarak, güvenilirliği ise iç tutarlık ve yarıya bölme yöntemleri kullanılarak değerlendirildi. Bulgular: Ölçeğin kapsam geçerliği indeksi %98.54 olarak bulundu. Faktör analizi sonucunda özdeğeri bir ve üzeri olan toplam varyansın %65.57’sini açıklayan dört faktör elde edildi. Ölçeğin Cronbach’s Alfa değeri 0.93 olarak belirlendi. Yarıya bölme yöntemi sonucunda ise ilk yarının Cronbach’s Alfa değeri 0.88; ikinci yarının ise 0.89 olarak belirlendi ve Guttman Cronbach’s Alfa değeri 0.83 olarak bulundu. Sonuç: Tüm analizlerin sonucunda 24 maddeden oluşan dörtlü likert tipi bir ölçek geliştirildi. Ölçeğin değerlendirmesi ortalama puan hesaplanarak belirlenmekte olup, ölçekten alınacak en düşük puan 0 ve en yüksek puan 3’tür. Alınan puan 0’a yaklaştıkça uyum seviyesi yükselir. Bu çalışmada ölçeğin iyi bir geçerlik ve güvenirliğe sahip olduğu belirlendi. Ölçeğin yaşlılarda uyum güçlüklerini belirlemek için kullanılması önerilir.
Keywords: Adaptation; elderly; nursing model; reliability; validity.; Adaptasyon; yaşlı; hemşirelik modeli; geçerlik; güvenirlik